(untitled) (E Global Congress, 2024)
This article examines the impact of technological advancements and computational methods on the analysis of semantic associations in scientific language. By leveraging corpus linguistics, natural language processing, and machine learning, the study reveals how scientific discourse has evolved in response to new technologies, reshaping the way scientific knowledge is constructed and communicated.